Health System Transformation Playbook and Unified Care Model: an integrated design, systems & complexity thinking approach to health system transformation - Teo, Ken Wah; Hu, Yun; Chew, Kwee Tiang; Pek, Wee Yang; Chua, Hong Choon; Matchar, David Bruce; Ng, Yeuk Fan (Frontiers in Health Services, 2023)
Health system transformation is a complex journey that often results in unintended consequences. Existing methods to drive health system transformation have intrinsic limitations which impede successful implementation in local contexts. The Health System Transformation Playbook is a design-, systems-, and complexity-thinking enabled methodology to systematically design, prioritize and test health system and services transformation actions, anchored on iterative story telling, model building and pathfinding processes that tackles the scale of socially and technologically complex adaptive systems through time. The Unified Care Model and its associated cascade of models are examples of ongoing application of Health System Transformation Playbook in a regional population health system in Singapore. Use of Health System Transformation Playbook enables stewards of health systems to gain a more systematic and coherent understanding of health systems and services planning and organization development, to accelerate transformation towards peoplecentered, integrated and value-driven health systems.